Polityka rodzinna Polski a Evangelium vitae - Gębka, Mikołaj (Teologia i Moralność, 2018)
The encyclical Evangelium Vitae underlines the importance of family policy in the context of – among others – demographics. The demographic situation of Poland is particularly unfavourable (in the 21st century TFR fluctuated between 1,2 and 1,4). After 1989 no coherent, well-planned family policy was developed in Poland, and it was only in the last decade when some positive changes started to occur. Changes in the legislation regarding maternity leaves and childcare and the introduction of the new “Family 500+” benefit in 2016 can be listed among promising solutions. One can already note the positive effects of some of these changes, such as the increased number of births.